Western Diet: Implications for Brain Function and Behavior - López-Taboada, Isabel; González-Pardo, Héctor; Conejo, Nélida María (Frontiers in Psychology, 2020)
Western diet (WD) pattern characterized by high daily intake of saturated fats and refined carbohydrates often leads to obesity and overweight, and it has been linked to cognitive impairment and emotional disorders both in animal models and humans. This dietary pattern alters the composition of gut microbiota influencing brain function by different mechanisms involving the gut-brain axis. In addition, long-term exposure to highly palatable foods typical of WD could induce addictive-like eating behavior and hypothalamic-pituitary-adrenal axis dysregulation associated with chronic stress, anxiety, and depression. In turn, chronic stress modulates eating behavior and it could have detrimental effects on different brain regions like the hippocampus, the hypothalamus, the amygdala, and several cortical regions. Moreover, obesity and overweight induce neuroinflammation and increase oxidative stress causing neuronal and glial cell dysfunction. In this review, we summarize the current scientific evidence about the mechanisms and factors relating WD consumption with altered brain function and behavior. Possible therapeutic interventions and limitations are also discussed, aiming to tackle and prevent this current pandemic.